The triad of knowledge: Systematic, diversity and conservation status of the Mexican species of Tabernaemontana (Apocynaceae; Rauvolfioideae: tribe Tabernaemontaneae) - Alvarado-Cárdenas, Leonardo O.; Lozada-Pérez, Lucio; Cadena R., Joselin; Islas-Hernández, Sofia; Martínez-González, C. Ramiro; Cortez C., Ericka B.; González-Martínez, César A.; González-Ramírez, Ixchel S. (Phytotaxa, 2019)
In this study, we update the systematics of the Tabernaemontana and describe the general patterns of species diversity and conservation status in Mexico. A total of 18 species were registered, including one cultivated species, two new species described here (T. chamelensis L.O. Alvarado & Lozada-Pérez and T. ochoterenae L.O. Alvarado & S. Islas), and eight species endemic to Mexico, which in total represents 47% of the diversity of the genus in the country. The states of Chiapas, Oaxaca, and Veracruz had the highest species diversity in native and endemic species. A map based on the kriging approach and the sums of species distribution models corroborate the sites of high diversity. A comparison among American countries showed that Central American countries share more specific similarity than South American ones. A risk evaluation showed that six species are under threat, mainly the endemic species. This exercise demonstrated that this genus is an interesting model to understand the biogeography, evolution, and affinities of the tropical flora of the Americas. Our work provides a basis for a deeper study of the biogeography and biology of the members of genus Tabernaemontana.